2001
DOI: 10.1002/j.2164-490x.2001.tb00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Recollections: A Humanistic Assessment in Counseling

Abstract: As a projective technique, early recollections help counselors understand the uniqueness and potential of individuals through an empathic interaction in counseling. A case presentation illustrates the use of early recollections in counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Another more reality‐bound engagement of a counselor's imaginative faculty occurs when listening to a client recount his or her early recollections as a projective technique (Clark, 2001, 2002, 2013). In various other projective techniques, it is an act of imagination for the counselor to envision a client's productions relating to such examples as the inkblot associations on the Rorschach or to narrations elicited by the picture stimulus properties of the Thematic Apperception Test (Clark, 1995; Singer, 1981).…”
Section: Counseling Implications Of Imaginationmentioning
confidence: 99%
“…Another more reality‐bound engagement of a counselor's imaginative faculty occurs when listening to a client recount his or her early recollections as a projective technique (Clark, 2001, 2002, 2013). In various other projective techniques, it is an act of imagination for the counselor to envision a client's productions relating to such examples as the inkblot associations on the Rorschach or to narrations elicited by the picture stimulus properties of the Thematic Apperception Test (Clark, 1995; Singer, 1981).…”
Section: Counseling Implications Of Imaginationmentioning
confidence: 99%
“…This description took as its basis the compatibility of the particular action emphasized by the client in their recollection with the action-content emphasized in the life style as recommended by the literature. Similarly, the suggestion of the literature to pay attention to the action stated in the first sentence of the individual's narrative was also followed (Clark, 2001;Maree, 2013).…”
Section: Fourth Step: Comparison Of the Early Recollection Narratives And Life Style Content Obtained Through The Adlerian Interviewsmentioning
confidence: 97%
“…In the relevant literature, to use the content provided by early recollection experiences in terms of a client's contextual assessment is highly valued in psychological counseling. Sharing these experiences in a counseling setting is regarded as a highly valuable technique in terms of empathetic interaction (Clark, 2001;Kaplan, 1985). While the early recollections and life-style experiences, as well as the relationship between these, have been included to date in various studies in the relevant literature, no study in the Turkish literature has yet to discuss this.…”
mentioning
confidence: 99%
“…The early memories question prompts the client to remember three early memories from childhood. Clark (2002) indicated that clients usually do not disclose traumatic events when requested to report early recollections, and if the client does focus on traumatic events this may be an indication that the trauma is a significant part of the individual's personality construction similar to the results reported by Berntsen and Rubin (2006). This can create a dilemma for the client in wanting to engage in the process, but also wanting to avoid triggering traumatic reactions.…”
Section: Recommendations For Alternate Promptsmentioning
confidence: 99%